PENGARUH MODEL PEMBELAJARAN BERDIFERENSIASI BERBASIS PjBL TERHADAP MOTIVASI BELAJAR DAN LITERASI DIGITAL SISWA DI SEKOLAH DASAR - Sartika, Dewi Sartika; Abustang, Perawati Bte; Fatimah, Waddi; Amaliyah, Nurhadifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of a differentiated learning model based on Project Based Learning (PjBL) on students' learning motivation and digital literacy in elementary schools. This study is motivated by the importance of implementing learning that can accommodate differences in student learning needs and increase learning motivation and digital literacy. The differentiated learning model based on PjBL is seen as being able to provide a meaningful, active learning experience that is in accordance with student characteristics. This study uses a quantitative approach with an ex post facto research type. The study population was all fourth and fifth grade students of SD Inpres Tangalla. The research sample was determined using a stratified random sampling technique. The instruments used were a questionnaire on the application of the differentiated learning model based on PjBL, a learning motivation questionnaire, and a digital literacy questionnaire. Data were analyzed using analysis prerequisite tests including normality, homogeneity, and linearity tests, followed by hypothesis testing using Multivariate Analysis of Variance (MANOVA). The results showed that the differentiated learning model based on PjBL had a significant effect on students' learning motivation and digital literacy. This is proven through the results of the Multivariate Tests which obtained a significance value of 0.002 < 0.05. In addition, the results of the Tests of Between-Subjects Effects showed that the differentiated learning model based on Project Based Learning (PjBL) had a significant effect on learning motivation with a significance value of 0.004 < 0.05 and on digital literacy with a significance value of 0.002 < 0.05. Thus, it can be concluded that the implementation of the differentiated learning model based on Project Based Learning (PjBL) has a significant effect on learning motivation and digital literacy of students in elementary schools.